2019
DOI: 10.1111/medu.13891
|View full text |Cite
|
Sign up to set email alerts
|

‘Bumping along’: a qualitative metasynthesis of challenges to interprofessional placements

Abstract: Context Interprofessional practice is required to manage complex health care needs globally. It is well established that interprofessional placements (IPP) prepare students to work collaboratively, yet IPP implementation remains limited and disjointed. Objectives This review synthesised student, educator and service user perspectives in order to better understand challenges of IPP and provide recommendations for sustainable IPP implementation. Methods A systematic metasynthesis of qualitative literature source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 86 publications
(219 reference statements)
1
18
0
Order By: Relevance
“…The full search strategy is available in an additional word file [see Additional file 1]. In addition, we included articles found in the reference lists of previous reviews on IPE, discovered as a result of the search for IPE interventions [4,6,9,[14][15][16][17][18][19][20][21][22].…”
Section: Data Sources and Selection Criteriamentioning
confidence: 99%
“…The full search strategy is available in an additional word file [see Additional file 1]. In addition, we included articles found in the reference lists of previous reviews on IPE, discovered as a result of the search for IPE interventions [4,6,9,[14][15][16][17][18][19][20][21][22].…”
Section: Data Sources and Selection Criteriamentioning
confidence: 99%
“…The students are active participants, and they learn with and from each other in authentic activities [ 5 ]. The groups often consist of nursing and medicine students overlapping with physiotherapy and occupational therapy students [ 2 , 6 , 7 ]. IPE can consist of a wide range of activities depending on the aims, educational setting, and availability of participants.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have systematically mapped IPE [ 2 , 6 8 ], and have shown that setting and context matters [ 8 ] and contextual factors influence IPE [ 9 ]. Therefore, in each activity developed and implemented in different contexts the students’ experiences should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Geographical [ 21 ] and specific healthcare needs and resources [ 22 ] likely influenced the approach taken in these regions. Globally, long-term funding for practice-based IPE is an on-going challenge [ 23 ] and many practice-based IPE projects do not extend beyond pilot or short-term initiatives [ 24 ]. This has stimulated growing interest in relatively low resource activities such as case-based tutorials [ 25 – 27 ].…”
Section: Introductionmentioning
confidence: 99%